The specification of a small commercial wind energy conversion system for the South African Antarctic Research Base SANAE IV - Stander, Johan Nico (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--Stellenbosch University, 2008.